Laminated windshield breakage modelling in the context of headform impact homologation tests - Kosiński, Piotr; Osiński, J. (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of modelling a laminated windshield using the FEM is to provide a critical look on the way the adult headform impact tests are conducted in the process of motor vehicle certification. The main aim of the study is to modify the design of a laminated windshield in the context of a vehicle collision with vulnerable road users. The initial phase of the work was to develop a model of the adult headform impactor. The validation consisted in conducting a series of FEM analyses of the impactor certification testing according to the Regulation (EC) 631/2009.
Keywords: laminated windshield; polyvinyl butyral; fracture mechanics; pedestrian safety; dynamic analysis